Sharing ownership via employee stock ownership - James C. Sesil; Douglas L. Kruse; Joseph R. Blasi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Increased equity participation by employees has attracted substantial interest for its potential to affect both economic outcomes (e.g., worker and firm performance) and social outcomes (e.g., wealth and income inequality). This paper summarizes the findings from over 50 large-sample empirical studies that have been done on employee ownership and broad-based stock option plans in the past 25 years, covering studies on plan adoption, employee attitudes and behaviours, firm performance, and employee wages and wealth. The results from these studies indicate employee ownership is linked to better outcomes on average but employee ownership clearly does not automatically improve worker and firm outcomes given that there are both positive and neutral findings. Additional research is needed to determine the conditions under which employee ownership improves economic outcomes, to examine worker and employer concerns and the trade-offs they are willing to make, and to explore the further potential of these systems.
Keywords: D23; J32; J3; 330; broad-based stock options; employee ownership; incentive compensation; Arbeitnehmerbeteiligung; Welt